EVALUASI AKUNTANSI PERTANGGUNGJAWABAN DALAM MENILAI KINERJA MANAJEMEN - Pravitasari, Wenda Maretha Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out how far the companies in implementing the accounting responsibility which function as planning, cost preparation and management achievement appraisal are. The object of the research is PT Tuffiadi Semesta Surabaya. Qualitative method is applied as the method of research and descriptive analysis technique. The result of research shows that the budgeting system of PT Tuffiadi Semesta Surabaya is done by using bottom up method which is started by analyzing the lower-level managers to the upper-level managers who involve in the budgeting. The company cannot be said perfectly well in preparing the budgeting system since it has not separated the controllable and uncontrollable cost which causes the indistinct search of managerâs responsibility for incurred cost so it will affect on the weakening of cost control. In the implementation of accounting responsibility, budgeting should be prepared in appropriate with the level of responsibility centers in the company. Therefore the company should implement the accounting responsibility system in accordance with the applied rules. Keywords: Accounting Responsibility, Controllable and Uncontrollable Cost, Performance Appraisal